2016
DOI: 10.1111/jopr.12476
|View full text |Cite
|
Sign up to set email alerts
|

Digital Relief of the Mental Foramen for a CAD/CAM‐Fabricated Mandibular Denture

Abstract: Relief of the intaglio surface of a denture base is conventionally performed using thin wax and soft metal foil attached to the master cast. The following report highlights a new relief procedure for the mental foramen using a CT double scan technique on the CAD/CAM dentures fabricated for the patient with paresthesia of the left lower lip and chin during mastication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“… 22,28 However, the in vitro outcomes cannot be easily interpreted to confirm the adequacy of IOS as the final impression for all scenarios of removable denture fabrication. Further, the IOS systems can register the soft tissue only in their mucostatic state, which leaves the implementation of relief and pressure to the later stage of the denture design 37 . Potentially, this might lead to more denture post‐insertion sore spots and adjustments.…”
Section: Discussionmentioning
confidence: 99%
“… 22,28 However, the in vitro outcomes cannot be easily interpreted to confirm the adequacy of IOS as the final impression for all scenarios of removable denture fabrication. Further, the IOS systems can register the soft tissue only in their mucostatic state, which leaves the implementation of relief and pressure to the later stage of the denture design 37 . Potentially, this might lead to more denture post‐insertion sore spots and adjustments.…”
Section: Discussionmentioning
confidence: 99%
“…However, relief and pressure are possible after data digitalization. Okubo et al reported the CAD/CAM fabrication of a mandibular complete denture in which digital relief of the mental foramen was performed [36]. In the partial edentulous arch, in order to compensate for the difference in the amount of tissue displacement between the residual teeth and the residual mucous membrane, digital pressurization of the acquired residual mucous membrane data is required.…”
Section: Discussionmentioning
confidence: 99%
“…The first two companies to commercialize CAD/CAM dentures were Avadent and Dentca, with each taking a different approach to fabrication, milling, and 3D printing. Their processes and applications have been reviewed and described in the literature . The popularity and interest in CAD/CAM complete dentures is increasing.…”
mentioning
confidence: 99%